Analisis dan Desain Sistem Drainase di Lingkungan Universitas Lampung (Studi Kasus: Zona III Wilayah Rektorat – Fakultas Pertanian) - Effendi, Rahmat; Purwadi, Ofik Taufik; Herison, Ahmad (Universitas Lampung, 2018)
Water problems consist of three types: flood, drought, and water pollution. Floods are recognized as a significant source of threat to human life. One of the flood prevention actions that can be done is to optimize the drainage channels. Drainage can be defined as a technical action to reduce excess water so that the function of the area or land is not disturbed. University of Lampung is one of the locations prone to flooding. Therefore, a research to overcome the flood that occurred at the University of Lampung has been conducted (Case Study: Zone III Rectorate Area - Faculty of Agriculture). The purposes of this research are to analyze the drainage system of University of Lampung and to design drainage system that fulfill flood discharge plan. The research was conducted by survey in the field. The analysis conducted in this study include hydrological analysis and hydraulics analysis using HEC-RAS4.1.0 application. Calculation of discharge plan using rational method.. Based on the analysis results, there are no channels that are not sufficient for flood discharge, but there are some channels that are disconnected and cause the water to not flow. The disconnected channels are located on the channel with the DN5 and DN62 codes. For that, it is recommended to create a channel connecting DN62 channel with DN63, and make a channel on channel DN5 to DN65. The budget required for the repair of this channel is Rp 207,203,725.00 (Two Hundred Seven Million Two Hundred and Three Thousand Seven Hundred Twenty Five Rupiah).Keywords: Drainage, HEC-RAS, hydrology, hydraulics, floods